Intraoperative performance and ultrastructural integrity of human capsulotomies created by the improved precision pulse capsulotomy device. Issue 11 (November 2018) - Hooshmand, Joobin; Abell, Robin G.; Allen, Penny; Goemann, Karsten; Vote, Brendan J.
Abstract : Purpose : To investigate the intraoperative performance and the ultrastructural features of anterior capsulotomy performed with the improved Zepto precision pulse capsulotomy (PPC) device. Setting : Launceston Eye Institute, Launceston, Tasmania, Australia. Design : Prospective, consecutive case series. Methods : Intraoperative observation of performance and complications were made on consecutive eyes having capsulotomies with the improved PPC device. The capsulotomy specimens were examined under scanning electron microscope and compared with manual continuous curvilinear capsulorhexis and femtosecond laser–assisted cataract surgery specimens. Results : The study comprised 52 eyes. Intended capsulotomy occurred in 50 eyes with 2 device failures. Complete free‐floating capsulotomies were achieved in 48 eyes (96%). Anterior capsule tears occurred in 2 eyes (4%). Conclusions : The ability of the PPC device to create complete free‐floating capsulotomies improved; however, the radial tear rate remained high. The ultrastructural features in ex vivo human capsulotomy specimens still showed areas of irregular capsule margin with frayed edges.